High-Fat Diet—Shared Environmental Risk Factor for Amyotrophic Lateral Sclerosis and Multiple Sclerosis - Thomas Gabriel Schreiner; Liviu Iacob; Cristina Georgiana Croitoru; Diana Nicoleta Hodorog; Dan Iulian Cuciureanu (Sclerosis)
Background: Amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS) are, in essence, neurodegenerative disorders with significant individual, social, and economic burdens worldwide. Despite having different clinical onset and evolution, the two diseases share common risk factors and underlying pathophysiological mechanisms. Environmental risk factors are particularly interesting, considering the available effective counter strategies. High-fat diets remain a significant element that negatively impacts the onset and evolution of several disorders, including ALS and MS. Focusing on changeable disease-related aspects is increasingly appealing in the context of a lack of an effective treatment. Methods: This review aims to offer an updated overview of the influence of high-fat diets in modulating the risk of onset and progression of ALS and MS, based on the search of three relevant online databases. Results: In the first part, the shared pathophysiological mechanisms of ALS and MS are shown, and significant differences between the two disorders are highlighted. Subsequently, the most relevant research on this topic conducted in animal models and humans is presented, bringing additional proof of the critical role of high-fat diets in neurodegeneration. Finally, based on current knowledge, the authors offer potential therapeutic approaches and future relevant research directions to better control nutrition in ALS and MS patients, hoping to increase survival and quality of life. Conclusions: High-fat diets negatively impact the onset and evolution of ALS and MS.